(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The production of glued structures from modified wood materials is a promising direction. The strength of the adhesive joint depends on various factors, such as the type of wood materials, the type of glue, the humidity of the material, the gluing mode, etc. The article provides the results and analysis of the strength of the adhesive joint from various factors.